Digital Television and Its Digital Offshoots vs the Modern Viewer’s Expectations - Myślak, Dominika Agata (Media - Culture - Social Communication, 2019)
The author of this article presents selected issues connected with the functioning of television in the digital era and discusses important questions adhering to the digital television itself as well as Internet TV platforms. The media reality shown in TV programmes is analysed by the author, who pinpoints the dynamics as the main characteristics of both the precipitous development of technology in digital devices and rapidly changing expectations of the viewers who expect better quality and more diverse television offerings. According to the author, modern television has not said its final word and is a fundamental element of culture, which guarantees its longevity.